Pengaruh Angkatan Kerja Inflasi, Pengangguran, dan Kemiskinan Terhadap Pertumbuhan Ekonomi Di Indonesia Periode (2014-2023) - Arosyid Abrian Loka; Bina Alfiyya Shofaa; Wisnu Adji Nugroho; Muhammad Kurniawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze the influence of the labor force, inflation, unemployment and poverty on economic growth in Indonesia for the period (2014-2022). The variables used are Inflation as the dependent variable, Money Supply (JUB) and Interest Rates as the independent variables. The data used in this research is secondary data obtained from publications by the Indonesian Central Bureau of Statistics. The analytical method used is a multiple linear regression model or Ordinary Least Square (OLS). In processing the data, the author used the help of Eviews 10 software. Based on the estimation results, it was found that there is a relationship between Labor Force, Inflation, Unemployment and Poverty on economic growth in Indonesia and the variables Labor Force, Inflation, Unemployment and Poverty have a positive and significant effect on Economic Growth in Indonesia .